2002
DOI: 10.21273/hortsci.37.1.227
|View full text |Cite
|
Sign up to set email alerts
|

'AC Harrow Crisp' Pear

Abstract: had been removed by 1990 because of extensive fire blight damage. 'AC Harrow Crisp' out-yielded 'Anjou' and 'Bosc' in the first 5 years of an orchard planted at Summerland, B.C. (Table 1). Shoot. The bark on the sun-exposed side of dormant shoots is brown (RHS 165A, Royal Horticultural Society, 1966). Mean internode length of 'AC Harrow Crisp' was similar to 'Bartlett' and 'Harrow Sweet', but shorter than 'Harvest Queen' and 'Bosc' (Table 2). Leaves. The leaves are elliptic. The shape of the base of the leaf b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In summary, this study reports reproducible SSR data for 28 cultivars of the genus Pyrus Four Canadian cultivars ('Harrow Delight', 'AC Harrow Crisp', 'AC Harrow Gold', and 'Harvest Queen') are clustered in the same clade with strong support, consistent with their known pedigrees (Hunter et al, 2002a(Hunter et al, , 2002bQuamme and Spearman, 1983). The rootstock genotypes OHF 69, OHF 87, and OHF 333 also group together with moderate support.…”
Section: Cultivar Namesupporting
confidence: 66%
“…In summary, this study reports reproducible SSR data for 28 cultivars of the genus Pyrus Four Canadian cultivars ('Harrow Delight', 'AC Harrow Crisp', 'AC Harrow Gold', and 'Harvest Queen') are clustered in the same clade with strong support, consistent with their known pedigrees (Hunter et al, 2002a(Hunter et al, , 2002bQuamme and Spearman, 1983). The rootstock genotypes OHF 69, OHF 87, and OHF 333 also group together with moderate support.…”
Section: Cultivar Namesupporting
confidence: 66%
“…Our previous research revealed that 1-MCP and storage at 0 °C, 2.5 kPa O 2 and 2 kPa CO 2 effectively controls the development of senescent scald and internal breakdown in 'Swiss Bartlett' and 'Cold Snap' pears (Lum et al 2017). 'Cold Snap' and 'AC Harrow Crisp' are newly developed Ontario pear cultivars that are resistant to fire-blight (Hunter et al 2002(Hunter et al , 2009, which is an orchard-borne disease leading to widespread economic losses in the production of traditional cultivars, such as 'Bartlett'. 'AC Harrow Crisp' is a midseason pear with highly preferred flavour and texture properties (Hunter et al 2002).…”
mentioning
confidence: 99%
“…'Cold Snap' and 'AC Harrow Crisp' are newly developed Ontario pear cultivars that are resistant to fire-blight (Hunter et al 2002(Hunter et al , 2009, which is an orchard-borne disease leading to widespread economic losses in the production of traditional cultivars, such as 'Bartlett'. 'AC Harrow Crisp' is a midseason pear with highly preferred flavour and texture properties (Hunter et al 2002). Current storage recommendations indicate that pears of this cultivar can be cold stored for up to 4 months (DeEll and Slingerland 2012), but there is no knowledge on whether storability can be enhanced by 1-MCP and/or CA.…”
mentioning
confidence: 99%
“…Fire blight tolerance. Like with other introductions from the AAFC pear breeding program formerly located at Harrow (Hunter et al, 1992(Hunter et al, , 2002a(Hunter et al, , 2002bQuamme and Spearman, 1983), 'Harovin Sundown' has excellent resistance to fire blight (caused by E. amylovora), similar to or greater than that of 'Kieffer', which is used as the standard for selection (Hunter, 1993). Using natural fire blight infection scores (from van der Zwet et al, 1970), 'Harovin Sundown' had a resistance rating much greater than that of 'Bartlett' (Table 1).…”
mentioning
confidence: 98%
“…Pollen compatibility has been assessed using pollination records from the breeding program and from a limited number of crosses made specifically for this purpose using methods described earlier (Hunter et al, 2002a(Hunter et al, , 2002b. Generally, a fruit set of greater than 20% is required for commercial fruit production, whereas fruit set less than 10% suggests incompatibility.…”
mentioning
confidence: 99%